Thromboembolic and bleeding events in intensive care unit patients with COVID-19: results from a Brazilian tertiary hospital - Antonio Adolfo Guerra Soares Brandão (Elsevier, 2021)
ABSTRACT: Objectives: To describe the incidence of thromboembolic events in adult patients with severe COVID-19 and identify clinical and laboratory factors associated with these events. Design: Observational retrospective cohort study of 243 adult patients with severe COVID-19 admitted to an intensive care unit (ICU) at a Brazilian tertiary hospital. Results: The incidence of all thromboembolic events was 14.8%, in which 3.8% developed deep vein thrombosis, 7.8% pulmonary embolism, 2.5% acute myocardial infarction, 1.2% stroke, and 1.2% peripheral artery occlusion. Risk factors identified were D-dimer at admission >3000 ng/mL (P=<0.0013) and major bleeding (P=0.001). The cumulative risk of developing thromboembolic events at day 28 after ICU admission was 16.0%. The rate of major bleeding was 4.1%. After receiver operating characteristic curve analysis, the D-dimer cut-off at admission correlating with thromboembolic events was 1140.5 ng/mL. Conclusions: The rate of thromboembolic events in our study was lower than previously described. High D-dimer level at admission was the leading risk factor; the optimal cut-off was 1140.5 ng/mL. The occurrence of thromboembolic events did not have an impact on the median overall survival rate. The optimal anticoagulant strategy in this context still needs to be established.